THE EVOLUTION OF SERVANT LEADERSHIP RESEARCH (2020-2024): A SYSTEMATIC REVIEW AND SOCIAL IMPACT ANALYSIS - Indarta, Yose; Sugriwaputra, Rikky Ariessetiawan; Saumadin; Mansuri; Faisal; Kate, Yerlin Tending; Palopo, Ari (Journal of Scientech Research and Development, 2024)
This systematic review examines the evolution of servant leadership research and practice from 2020 to 2024, analyzing 435 peer-reviewed articles from the Scopus database. The study employs a mixed-methods approach combining bibliometric analysis with qualitative content analysis to investigate emerging trends, sector-specific applications, and societal impact of servant leadership during a period marked by global disruption and organizational transformation. Findings reveal a significant increase in servant leadership adoption, particularly in healthcare (28%), education (22%), and technology sectors (20%), with distinct patterns of implementation across different organizational contexts. The analysis identifies three primary drivers of servant leadership effectiveness: crisis management, employee well-being, and service quality, with varying impact across sectors. Healthcare organizations demonstrate the highest adoption rate (Impact Score: 85 for crisis management), followed by educational institutions (Impact Score: 82 for employee well-being) and technology companies (Impact Score: 80 for service quality). The research also uncovers emerging trends in servant leadership application, including its role in digital transformation, environmental sustainability, and social justice initiatives. However, gaps persist in understanding servant leadership's effectiveness in virtual environments and its integration with emerging technologies. This study contributes to the theoretical development of servant leadership while providing practical insights for organizations seeking to implement this leadership approach in contemporary contexts. The findings suggest that servant leadership's emphasis on human development and ethical behavior makes it particularly relevant for addressing modern organizational challenges, though its implementation requires careful adaptation to specific contextual requirements.